Cysteine-free peptides in scorpion venom: geographical distribution, structure-function relationship and mode of action - Elgar, D; Du Plessis, J; Du Plessis, L (African journal of biotechnology, 2006)
Scorpion venoms are well known sources of Na super(+)-channel, K super(+)-channel, Cl super(-)-channel, Ca super(2+)-channel and ryanodine channel selective peptides. In 1993, the first cysteine-free peptide was isolated from scorpion venom. Within the last six years, cysteine-free peptides with and without antimicrobial activity have been isolated from scorpion venom. The first antimicrobial peptides being parabutoporin and hadrurin, after which nine more have followed. Characteristics of these peptides include pore-formation and/or antimicrobial activity. Six peptides of similar structures without antimicrobial activity have also been isolated. Two of these peptides have bradykinin-potentiating functions. The functions of the other four are unknown. These peptides have the potential to combat cancer, a variety of skin or wound bacterial and fungal infections. This review will focus on the primary and secondary structures as well as reported functions and applications of the cysteine-free peptides identified in scorpion venom.